Importance of the Reducing Agent in Direct Reductive Heck Reactions. Issue 1 (30th November 2017) - Raoufmoghaddam, Saeed; Mannathan, Subramaniyan; Minnaard, Adriaan J.; de Vries, Johannes G.; de Bruin, Bas; Reek, Joost N. H.
Abstract: The role of the reductant in the palladium N‐heterocyclic carbene (NHC) catalyzed reductive Heck reaction and its effect on the mechanism of the reaction is reported. For the first time in this type of transformation, the palladium‐NHC‐catalyzed reductive Heck reaction was shown to proceed in the presence of LiOMe and i PrOH even at 10 °C to give the products very efficiently in excellent yields and with exceptional chemoselectivities. This study shows that the reaction proceeds through two distinct mechanisms that depend on the nature of the reducing agent. In the presence of a protic solvent or acidic medium the reaction undergoes protonation to yield the reduced product, whereas in the absence of proton source, it proceeds through the insertion of the reductant followed by reductive elimination. The kinetic data reveal that the oxidative addition is the rate‐determining step in the reaction. The reaction profiles show first‐order kinetics in aryl iodide and Pd and zero‐order kinetics in LiOMe, benzylideneacetone, and the excess amount of NHC ligand. In addition, the reaction progress kinetic analysis shows that neither catalyst decomposition nor product inhibition occurs during the reaction. DFT calculations of the key steps confirm that the oxidative addition step is the rate‐determining step in the reaction. Deuterium‐labeling experiments indicate that the product is formed by the protonation of the Pd−Calkyl bond of the intermediate formed after enone insertion into the Pd−CAr bond. Application of chiral NHC ligands in the asymmetric reductive Heck reaction only results in poor enantioselectivities (enantiomeric excess up to 20 %) and is also substrate specific. DFT calculations suggest that the migration of the aryl group to the alkene of the substrate is the enantioselectivity‐determining step of the reaction. It is further shown that if the steric bulk at the enone is small (a methyl group), the two transition state barriers from [Pd II (L 2 )(ArI)(enone)] species C re and C si, which have the re and si face of the enone substrate coordinated to Pd, are very similar, in line with the experimental results. With a slightly larger group (an isopropyl substituent) a significant difference in energy barriers is calculated (2.6 kcal mol −1 ), and in the experiment this product is formed with a modest enantiomeric excess (up to 20 %). Abstract : Double agent : The palladium N‐heterocyclic carbene catalyzed reductive Heck reaction proceeds in the presence of LiOMe and i PrOH even at 10 °C to give the products very efficiently in excellent yields and with exceptional chemoselectivities. This study shows that the reaction proceeds through two distinct mechanisms that depend on the nature of the reducing agent.